A geometric numerical integration method for solving the Volterra integro-differential equations - Hashemi, M. S.; Darvishi, E.; İnç, Mustafa (Taylor & Francis Ltd, 2018)
In this paper, a geometric approach is proposed to the integration of the system of Volterra integro-differential equations (IDEs). To do this, the equivalent system of ordinary differential equations of IDEs are obtained and converted into a Lie type augmented dynamical system. Then we construct the group preserving scheme (GPS) on the system of Volterra IDEs which is formulated by an exponential mapping to keep the group properties of . Some linear and nonlinear examples are solved as a description for the power and efficiency of GPS. Finally, in order to demonstrate the validity and efficiency of the present method, the convergency is numerically discussed and accuracy of results are compared with the reported results in the literature.
Keywords: Group preserving scheme; Minkowski space; Volterra integro-differential equation